Touraine-Solente-Gole syndrome: The complete form needs to be recognized - Karnan, Sudha (Medknow Publications & Media Pvt Ltd, 2012)
The primary hypertrophic osteoarthropathy (HOA) (pachydermoperiostosis) is a rare hereditary disease characterized by skin manifestations (pachydermia), digital clubbing and proliferation of periosteum (periostitis) with sub-periosteal new bone formation. We describe here a case who presented with seborrheic dermatitis and joint pain of both hands on work up matched satisfactorily with the complete form of primary HOA. The identification of secondary form being relatively common among clinicians and hence the importance of recognizing the primary form, which is a difficult to treat condition is discussed here.